Another new and threatened species of lancehead genus Bothrops (Serpentes, Viperidae) from Ilha dos Franceses, Southeastern Brazil - Barbo, Fausto E.; Gasparini, João Luiz; Almeida, Antonio P.; Zaher, Hussam; Grazziotin, Felipe G.; Gusmão, Rodrigo B.; Ferrarini, José Mário G.; Sawaya, Ricardo J. (Zootaxa, 2016)
A new insular species of the genus Bothrops is described from Ilha dos Franceses, a small island off the coast of Espírito Santo State, in southeastern Brazil. The new species differs from mainland populations of B. jararaca mainly by its small size, relative longer tail, relative smaller head length, and relative larger eyes. The new species is distinguished from B. alcatraz, B. insularis and B. otavioi by the higher number of ventral and subcaudal scales, relative longer tail and smaller head. The new species is highly abundant on the island, being nocturnal, semiarboreal, and feeding on small lizards and centipeds. Due its unique and restricted area of occurrence, declining quality of habitat, and constant use of the island for tourism, the new species may be considered as critically endangered.